Sanksi Pidana Bagi Influencer Yang Melakukan Penipuan Investasi Berkedok Binary Option - Rahmat Rahmat; Juanrico Alfaromona Sumarez Titahelu; Elias Zadrach Leasa (PATTIMURA Law Study Review, 2023)
ABSTRACT: The crime of illegal binary option investment is very disturbing to the public by committing tricks and causing economic losses to victims of fraud which in turn makes victims report it and perpetrators such as influencers who carry out investment fraud under the guise of binary options. The purpose of this study is to discuss the application of rules and criminal sanctions for unscrupulous influencers who commit investment fraud under the guise of binary options. This research is a normative juridical research carried out using statutory, conceptual and case approaches. Fraudulent crimes committed by influencers to gain profit by offering binary option applications to the public who end up experiencing large losses, of course, must be sanctioned according to applicable regulations, from this the rules and criminal sanctions for influencers who commit fraud, have been listed in the Criminal Code Article 378 and Article 45 paragraph (2) of the ITE Law Jo Article 27 paragraph (2) regarding gambling content of the ITE Law. And also Article 45A paragraph (1) Jo Article 28 Paragraph (1) regarding fake news that harms consumers ITE Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, for this reason, based on a series of investigative investigations up to a decision at the district court level and the district high court, in the end, the judge handed down a verdict, the influencers, namely Doni Salamanan & Indra Kenz, were also subject to imprisonment with a sentence of 8 years in prison for influencer Doni Salmanan and 10 years in prison for influencer Indra Kenz for being proven to have committed fraud that harmed consumers, namely people who trade on binary option applications.